Ti-BTx implant and preparation method and application thereof
By constructing oxygen vacancies on the surface of barium titanate, inhibiting bacterial electron transport chains and promoting bone cell proliferation, the problem that existing implants are difficult to balance between antibacterial and promoting bone regeneration is solved, and effective inhibition of bacteria and regeneration of bone tissue is achieved.
Patent Information
- Application Number
- CN202411664821.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing implants are difficult to take into account both the antibacterial and the promotion of bone regeneration, resulting in the problem of implant infection and unhealing of fracture sites.
By constructing oxygen vacancies (BTx) on the surface of barium titanate (BT), the inhibitory effect of bacterial electron transport chains is used to block bacterial proliferation and biofilm formation, while promoting osteocyte proliferation through potential changes.
Effective inhibition of bacteria is achieved, the formation of bacterial biofilms is blocked, the risk of implant infection is reduced, and the proliferation of bone cells and the regeneration of bone tissue is promoted.
Smart Images

Figure CN119656387A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medical materials, and in particular relates to a Ti-BTx implant and a preparation method and application thereof. Background Art
[0002] Bone implant infection is a catastrophic surgical complication. The main cause of infection caused by implants is the adhesion and colonization of bacteria on their surface, which in turn forms a biofilm. Once a biofilm forms on the implant surface, it will eventually lead to implant failure due to persistent inflammation and necrosis of surrounding tissues. Due to bacterial resistance and limited drug penetration at the site of infection, the efficacy of systemic antibiotics is impaired, and bacterial infection seriously affects bone regeneration, causing patients to suffer from prolonged fractures and unbearable pain. Therefore, giving implants antibacterial properties, especially preventing biofilm formation, has become the key to solving implant infections.
[0003] At present, antibiotics are used clinically before and after surgery to prevent implant infection, but the effect is not good. Therefore, some studies have used gelatin and other materials to load antibiotics on the surface of implants to achieve slow release and antibacterial effects, thereby preventing implant infection. Although this solves the problem of low efficiency of systemic antibiotic use, it still cannot avoid the emergence of antibiotic resistance and super bacteria. In addition, some studies have used reactive oxygen free radicals (ROS) for antibacterial purposes, but they not only kill bacteria, but also aggravate cell aging, which is not conducive to tissue regeneration; and the production of ROS often requires external intervention, such as ultrasound or light stimulation, but there is currently no clinical method for diagnosis in the early stages of infection, so ROS antibacterial is a long way from clinical use. Whether it is antibiotics or ROS, although they can kill bacteria to a certain extent, they will inhibit the regeneration of bone tissue. Therefore, it is necessary to develop an implant coating that targets bacteria and does not affect cell proliferation, which can inhibit bacterial proliferation for a long time, thereby preventing implant infection and promoting bone tissue regeneration. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a Ti-BTx implant and a preparation method and application thereof, so as to solve the technical problem that the existing implants cannot achieve both osteogenesis and antibacterial effects.
[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a Ti-BTx implant, comprising the following steps: S1. The titanium sample is pickled to remove the natural oxide layer on the surface, and then the titanium sample is placed in an electrolyte for electrolytic oxidation for 1.5-2.5 hours to obtain a porous titanium implant; S2, dissolving the titanium salt in an organic solvent, and then adjusting the pH value to 5-7 to prevent the solution from hydrolyzing too quickly; then adding the barium salt solution to react for 0.5-2h, and finally adding ammonia water to react for 5-60min to obtain barium titanate sol; the ratio of titanium salt, barium salt and ammonia water is 0.1-0.3mol:0.1-0.3mol:10-50mL; S3. Immerse the porous titanium implant in the barium titanate sol and react for 12-48 hours to ensure that the sol fully penetrates into the porous structure. Then take out the sample and dry it at room temperature for 10-14 hours to allow the sol to gradually gel on the surface of the porous titanium. Ensure that the surface is evenly dried and a gel layer is formed. Then place the dried sample at 200-600°C for heat treatment for 3.5-6.5 hours, and finally slowly cool it to room temperature to avoid damage to the barium titanate coating structure due to rapid temperature changes, thereby obtaining a Ti-BTx implant.
[0006] On the basis of the above technical solution, the present invention can also be improved as follows: Furthermore, before the pickling treatment in step S1, the titanium sample is ultrasonically cleaned with ethanol and water in sequence (ultrasonic power is 1-3w, ultrasonic time is 5-15min) to remove impurities on the surface of the sample.
[0007] Furthermore, the pickling treatment is: washing the titanium sample with a 5-10wt% hydrofluoric acid solution for 3-5 times, and each washing time is 5-60s.
[0008] Furthermore, the electrolytic oxidation process is as follows: immersing the titanium sample as an anode and an inert metal as a cathode in an electrolyte with a distance of 5-20 cm between the anode and the cathode to ensure uniform current distribution, followed by electrolytic oxidation at a DC voltage of 40-60 V for 1.5-2.5 h.
[0009] Furthermore, the electrolyte is prepared by mixing ammonium fluoride, ethylene glycol and water in a ratio of 0.3-0.7 g: 90-100 mL: 3-7 mL.
[0010] Furthermore, the titanium salt is butyl titanate (Ti(OBu)4), isopropyl titanate or titanium tetrachloride; and the barium salt is barium nitrate (Ba(NO3)2), barium carbonate or barium acetate.
[0011] Furthermore, the reagent used to adjust the pH value is glacial acetic acid.
[0012] Furthermore, the heat treatment process is: first preheat the sample at 180-220°C for 1.5-2.5h to remove residual solvent and further solidify the gel layer; then set the reaction system to a protective atmosphere and sinter at 550-650°C for 2-4h.
[0013] Furthermore, the gas used in the protective atmosphere is argon or hydrogen.
[0014] Furthermore, the heating rate in the preheating stage is 2-5°C / min, and the heating rate in the sintering stage is 3-10°C / min.
[0015] Furthermore, the cooling rate during cooling is 3-5°C / min.
[0016] The invention also discloses a Ti-BTx implant prepared by the preparation method.
[0017] The invention also discloses the application of the Ti-BTx implant in the preparation of osteogenic materials.
[0018] The beneficial effects of the present invention are: 1. The present invention adopts a non-antibiotic strategy to prevent implant infection. It utilizes the rapid proliferation of bacteria during biofilm formation and constructs oxygen vacancies (BTx) on the surface of barium titanate (BT) through defect engineering, thereby increasing the material's effect on bacterial electrons and completely interfering with the bacterial electron transport chain. By inhibiting the electron transfer of the bacterial electron transport chain, it inhibits bacterial proliferation, hinders the formation of bacterial biofilm, and reduces implant infection.
[0019] 2. The Ti-BTx implant prepared by the present invention can not only inhibit bacterial proliferation, but also promote bone cell proliferation. Although BTx affects bacterial electron transfer, since cell electron transfer is located in mitochondria rather than cell membranes, BTx can promote bone cell proliferation through potential changes. By using the different mechanisms of action of oxygen vacancy piezoelectric materials on bacteria and cells, one substance can achieve two effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the SEM image of the Ti-BTx implant; Figure 2 This is the magnified SEM surface morphology of the Ti-BTx implant; Figure 3 The effect of sintering time on bacterial membrane potential capacity; Figure 4 Comparison of the antibacterial ability of Ti and Ti-BTx; Figure 5 The effect of Ti and Ti-BTx on the outer membrane potential of bacteria; Figure 6 Cell live-death staining diagram; Figure 7 The results are for the osteogenic ability of Ti-BTx. DETAILED DESCRIPTION
[0021] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
[0022] Example 1 A method for preparing a Ti-BTx implant comprises the following steps: S1. Ultrasonic cleaning of the titanium sample was performed with ethanol and deionized water in turn (ultrasonic power was 1w, ultrasonic time was 15min), followed by rinsing the titanium sample with 5wt% hydrofluoric acid solution for 5 times, each rinsing time was 5s, and then the titanium sample was used as the anode and platinum was used as the cathode (the distance between the cathode and the anode was 20cm) and immersed in an electrolyte (ammonium fluoride: ethylene glycol: water = 0.7g: 90mL: 7mL), and electrolytic oxidation was performed at a DC voltage of 40V for 2.5h. Finally, the sample surface was rinsed with deionized water and placed in nitrogen, and dried at 120°C for 2h to obtain a porous titanium implant; S2, dissolving 0.3 mol of butyl titanate in 50 mL of ethanol, and then adding glacial acetic acid to adjust the pH value of the solution to 7; then dissolving 0.1 mol of barium nitrate in 50 mL of deionized water, and then slowly dripping the barium nitrate solution into the butyl titanate solution to react for 2 hours, and finally adding 50 mL of ammonia water to react for 60 minutes to obtain barium titanate sol; S3. Immerse the porous titanium implant in barium titanate sol for reaction for 12 hours, then take out the sample and dry it at room temperature for 10 hours; then increase the temperature from room temperature to 220°C at a heating rate of 5°C / min, preheat the sample at this temperature for 1.5 hours, then set the reaction system to a hydrogen atmosphere, and continue to increase the temperature to 550°C at a heating rate of 3°C / min, and sinter at this temperature for 3 hours. After completing the heat treatment, slowly cool it to room temperature at a cooling rate of 3°C / min, and finally wash the reactant with water to obtain a Ti-BTx implant.
[0023] Example 2 A method for preparing a Ti-BTx implant comprises the following steps: S1. Ultrasonic cleaning of the titanium sample was performed with ethanol and deionized water in turn (ultrasonic power was 3w, ultrasonic time was 5min), and then the titanium sample was rinsed with 10wt% hydrofluoric acid solution for 3 times, each rinsing time was 60s, and then the titanium sample was used as the anode and platinum was used as the cathode (the distance between the cathode and the anode was 5cm) and immersed in the electrolyte (ammonium fluoride: ethylene glycol: water = 0.3g: 100mL: 3mL), and electrolytic oxidation was performed at a DC voltage of 60V for 1.5h. Finally, the sample surface was rinsed with deionized water and placed in nitrogen, and dried at 80°C for 12h to obtain a porous titanium implant; S2, dissolving 0.1 mol of butyl titanate in 50 mL of ethanol, and then adding glacial acetic acid to adjust the pH value of the solution to 5; then dissolving 0.3 mol of barium nitrate in 50 mL of deionized water, and then slowly dripping the barium nitrate solution into the butyl titanate solution to react for 0.5 h, and finally adding 10 mL of ammonia water to react for 5 min to obtain barium titanate sol; S3. Immerse the porous titanium implant in barium titanate sol for reaction for 48 hours, then take out the sample and dry it at room temperature for 14 hours; then increase the temperature from room temperature to 180°C at a heating rate of 2°C / min, preheat the sample at this temperature for 2.5 hours, then set the reaction system to an argon atmosphere, and continue to increase the temperature to 650°C at a heating rate of 10°C / min, and sinter at this temperature for 2 hours. After completing the heat treatment, slowly cool it to room temperature at a cooling rate of 5°C / min, and finally wash the reactant with water to obtain a Ti-BTx implant.
[0024] Example 3 A method for preparing a Ti-BTx implant comprises the following steps: S1. Ultrasonic cleaning of the titanium sample was performed with ethanol and deionized water in turn (ultrasonic power was 2w, ultrasonic time was 10min), followed by rinsing the titanium sample with 8wt% hydrofluoric acid solution for 4 times, each rinsing time was 30s, and then the titanium sample was used as the anode and platinum was used as the cathode (the distance between the cathode and the anode was 10cm) and immersed in an electrolyte (ammonium fluoride: ethylene glycol: water = 0.5g: 95mL: 5mL), and electrolytic oxidation was performed at a DC voltage of 50V for 2h. Finally, the sample surface was rinsed with deionized water and placed in nitrogen, and dried at 100°C for 7h to obtain a porous titanium implant; S2, dissolving 0.2 mol of butyl titanate in 50 mL of ethanol, and then adding glacial acetic acid to adjust the pH value of the solution to 6; then dissolving 0.2 mol of barium nitrate in 50 mL of deionized water, and then slowly dripping the barium nitrate solution into the butyl titanate solution to react for 1 hour, and finally adding 30 mL of ammonia water to react for 30 minutes to obtain barium titanate sol; S3. Immerse the porous titanium implant in barium titanate sol for reaction for 30 hours, then take out the sample and dry it at room temperature for 12 hours; then increase the temperature from room temperature to 200°C at a heating rate of 3°C / min, preheat the sample at this temperature for 2 hours, then set the reaction system to an argon atmosphere, and continue to increase the temperature to 600°C at a heating rate of 6°C / min, and sinter at this temperature for 4 hours. After completing the heat treatment, slowly cool it to room temperature at a cooling rate of 4°C / min, and finally wash the reactant with water to obtain a Ti-BTx implant.
[0025] Example 4 The difference between this embodiment and embodiment 3 is that the sintering time of step S3 is adjusted to 2 hours, and the other implementation conditions are the same as those of embodiment 3 to obtain a Ti-BTx implant.
[0026] Comparative Example The difference between this comparative example and Example 3 is that the sintering time of step S3 is adjusted to 1 hour, and the other implementation conditions are the same as those of Example 3 to obtain a Ti-BTx implant.
[0027] Experimental Example 1 Structural Characterization Taking Example 3 as an example, the Ti-BTx implant was characterized, and its SEM image is as follows: Figure 1 As shown in the figure, it can be seen that Ti has a microporous structure, which is conducive to implant fixation and cell adhesion. Figure 1 Zoom in to see more details of the Ti-BTx implant, such as Figure 2 As shown in the figure, it can be seen that the Ti-BTx implant was successfully synthesized, its morphology is close to spherical, and it is evenly distributed on the surface of the titanium implant, which is also conducive to the uniform effect of BTx on the bone.
[0028] The sintering time of step S3 is different, and the proportion of oxygen vacancies in the final product is also different. The Ti-BTx implants obtained in Example 3, Example 4 and the comparative example are compared to see how they affect the bacterial potential. Figure 3 As shown, the Ti-BTx formed by treatment at different times has different membrane potential changing abilities on bacteria. The more green it is, the greater the impact on the membrane potential. It can be seen that the Ti-BTx implant formed when the sintering time is 4h (Example 3) has a higher membrane potential changing ability, which increases the effect of the Ti-BTx material on bacterial electrons, completely interferes with the bacterial electron transport chain, and inhibits the electron transfer of the bacterial electron transport chain.
[0029] The Ti-BTx implant used in the following experiments is the Ti-BTx implant prepared in Example 3.
[0030] Experimental Example 2 Test of the performance of inhibiting biofilm formation The effect of Ti-BTx on Staphylococcus aureus (ATCC 25923) was evaluated by plate spreading method. The specific process was as follows: Ti-BTx implants were placed in 48-well plates and exposed to bacterial suspension (bacterial concentration was 2×10 7 CFU / mL) for 8 h, and then the colony forming units (cfu) were quantified by plating on agar plates at 37°C for 12 h. For further verification, bacteria were added to Ti and Ti-BTx, cultured at 37°C for 1 day, and then live / dead staining was performed using the live / dead BacLight activity kit. Figure 4 As shown, compared with the control group (Ti group) without forming oxygen vacancies, the Ti-BTx group (Ti-BTx implant prepared in Example 3) has a more obvious effect of inhibiting bacterial proliferation, indicating that the Ti-BTx implant prepared in the present invention has a good ability to inhibit biofilm formation in a simulated in vivo environment.
[0031] The bacterial membrane potential of Staphylococcus aureus was evaluated using DiBAC4 (3). A bacterial suspension of Staphylococcus aureus (5 × 10 7 CFU mL -1 ) were applied to Ti and Ti-BTx surfaces and incubated for 6 h, then the culture medium was replaced with LB medium containing DiBAC4 (3) (5 μM) and incubated at 37 °C for another 2 h. The bacterial outer membrane potential was evaluated by fluorescence imaging. Figure 5 As shown, it was found that the bacterial outer membrane potential changed after contact with Ti-BTx implants, which was due to the inhibition of electron transfer by BTx.
[0032] Experimental Example 3 Osteogenesis Performance Detection MC3T3-E1 osteoblasts were seeded onto the Ti-BTx surface and cultured in a 37°C incubator for 24 h. Figure 6) It can be found that green represents living cells, and there are no obvious dead cells in the Ti-BTx group, and BTx can also promote cell proliferation. ALP and ARS were then used to detect the osteogenic ability of Ti and Ti-BTx. MC3T3-E1 cells were seeded into each well of a 12-well plate. When the cell confluence reached 70%, the α-MEM medium was replaced with an osteogenic induction medium containing 10mM β-glycerophosphate 50µg / mL ascorbic acid (Sigma), 50µg / mL ascorbic acid 10 mM β-glycerophosphate (Sigma) and 10 nM dexamethasone (Sigma) to promote the osteogenic ability of MC3T3-E1 osteoblasts and implants. The osteoinduction medium was renewed every 3 days together with the materials, and the activity of ALP was evaluated on days 7 and 14 using a 5-bromo-4-chloro-3-indoleyl phosphate / nitro blue tetrazolium (BCIP / NBT) ALP colorimetric kit (Beyotime, China). To evaluate the calcified extracellular matrix, the cells were fixed and treated with ARS dye (Beyotime, China), and ARS was measured on the 14th day. The images were captured using a scanner after removing the excess dye. The more red there is, the more ARS there is and the better the osteogenic ability. The staining images show that the Ti-BTx implant has a good osteogenic ability (e.g. Figure 7 ).
Claims
1. A method for preparing a Ti-BTx implant, characterized in that: The following steps are involved: S1, pickling the titanium sample, and then placing the titanium sample in an electrolyte for electrolytic oxidation for 1.5-2.5 hours to obtain a porous titanium implant; S2, dissolving the titanium salt in an organic solvent, then adjusting the pH value to 5-7, then adding the barium salt solution to react for 0.5-2h, and finally adding ammonia water to react for 5-60min to obtain a barium titanate sol; the ratio of the titanium salt, the barium salt and the ammonia water is 0.1-0.3mol:0.1-0.3mol:10-50mL; S3. Immerse the porous titanium implant in barium titanate sol to react for 12-48 hours, then take out the sample and dry it at room temperature for 10-14 hours, then place the dried sample at 200-600°C for heat treatment for 3.5-6.5 hours, and finally cool it to room temperature to obtain a Ti-BTx implant.
2. The method for preparing a Ti-BTx implant according to claim 1, characterized in that: The pickling treatment is: washing the titanium sample with a 5-10wt% hydrofluoric acid solution for 3-5 times, and each washing time is 5-60s.
3. The method for preparing the Ti-BTx implant according to claim 1, characterized in that: The electrolytic oxidation process is as follows: immersing the titanium sample as an anode and an inert metal as a cathode in an electrolyte, with the distance between the anode and the cathode being 5-20 cm, and then electrolytically oxidizing for 1.5-2.5 hours at a DC voltage of 40-60 V.
4. The method for preparing a Ti-BTx implant according to claim 3, characterized in that: The electrolyte is prepared by mixing ammonium fluoride, ethylene glycol and water in a ratio of 0.3-0.7 g: 90-100 mL: 3-7 mL.
5. The method for preparing a Ti-BTx implant according to claim 1, characterized in that: The titanium salt is butyl titanate, isopropyl titanate or titanium tetrachloride; the barium salt is barium nitrate, barium carbonate or barium acetate.
6. The method for preparing a Ti-BTx implant according to claim 1, characterized in that: The heat treatment process is as follows: firstly preheat the sample at 180-220° C. for 1.5-2.5 hours, then set the reaction system to a protective atmosphere, and sinter at 550-650° C. for 2-4 hours.
7. The method for preparing a Ti-BTx implant according to claim 6, characterized in that: The heating rate in the preheating stage is 2-5°C / min, and the heating rate in the sintering stage is 3-10°C / min.
8. The method for preparing a Ti-BTx implant according to claim 1, characterized in that: The cooling rate during the cooling is 3-5°C / min.
9. A Ti-BTx implant, characterized in that: The Ti-BTx implant is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the Ti-BTx implant according to claim 9 in preparing osteogenic materials.
Citation Information
Patent Citations
EBM molded titanium implant and preparation method and application thereof
CN109234735A
Preparation method for super-hydrophilic micro-nano surface of 3D printing nickel-titanium implant
CN115055697A
Preparation method of efficient piezoelectric coating on surface of titanium implant
CN116288287A